O arranjo com atualização na performace de música popular: análises de versões do Corta-Jaca de Chiquinha Gonzaga - Guilherme Braga Veroneze Gomes (2019)
We present a research of the qualitative type, in the field of studies of Musical Performance, whose object is to study three versions of the song Gaúcho (Corta-Jaca) by Chiquinha Gonzaga. As a source of data collection, we used transcription methods from phonograms as well as semi-structured interviews with the musicians responsible for the versions. With the data, we perform musical analysis from the point of view of the arrangement of the versions. As a comparative pole for the analyses, we elaborated a theme for the Corta-Jaca, and the process of elaboration of the same is also exposed in the work. We seek to understand, through analysis, how each performer relates theme and arrangement, resulting in a version, or an update of the song. To support our research, we will discuss the concepts of original, version, theme and arrangement in the context of popular music. As a practical result, we will present arrangements elaborated from the arrangement practices found in the analyzed material.